2016
DOI: 10.1016/j.ebiom.2016.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of G0/G1 Switch 2 Ameliorates Renal Inflammation in Chronic Kidney Disease

Abstract: Chronic kidney disease (CKD) is a global health problem, and novel therapies to treat CKD are urgently needed. Here, we show that inhibition of G0/G1 switch 2 (G0s2) ameliorates renal inflammation in a mouse model of CKD. Renal expression of chemokine (C-C motif) ligand 2 (Ccl2) was increased in response to p65 activation in the kidneys of wild-type 5/6 nephrectomy (5/6Nx) mice. Moreover, 5/6Nx Clk/Clk mice, which carry homozygous mutations in the gene encoding circadian locomotor output cycles kaput (CLOCK), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…We then measured the mRNA expression of these potential candidates in HSCs purified from Angptl2 fl/fl and Cdh5-Cre;Angptl2 fl/fl or Tie2-Cre;Angptl2 fl/fl mice and demonstrated that G0s2 was markedly decreased in both cKO mice (Figure 4A and Figure S4E). It has been reported that G0S2 is a multifaceted protein with disparate roles in proliferation, metabolism, inflammation and carcinogenesis [42][43][44] . G0s2 also regulates the cell cycle by either suspending cells in G0 phase or enhancing the G1-S switch under different physiological conditions 45 .…”
Section: Angptl2 Sustains the Level Of G0s2 To Support Hsc Activitiesmentioning
confidence: 99%
“…We then measured the mRNA expression of these potential candidates in HSCs purified from Angptl2 fl/fl and Cdh5-Cre;Angptl2 fl/fl or Tie2-Cre;Angptl2 fl/fl mice and demonstrated that G0s2 was markedly decreased in both cKO mice (Figure 4A and Figure S4E). It has been reported that G0S2 is a multifaceted protein with disparate roles in proliferation, metabolism, inflammation and carcinogenesis [42][43][44] . G0s2 also regulates the cell cycle by either suspending cells in G0 phase or enhancing the G1-S switch under different physiological conditions 45 .…”
Section: Angptl2 Sustains the Level Of G0s2 To Support Hsc Activitiesmentioning
confidence: 99%
“…In contrast to these previous reports, we found that heart failure in 5/6Nx mice was associated with the continuous increase in the expression levels of Clock and Arntl in circulating monocytes. As 5/6Nx-induced renal inflammation was alleviated in Clk / Clk mice 24 , CLOCK protein may promote the CKD-induced inflammatory response. The difference between previous studies and ours suggests that maintenance of normal Clock gene function is important to prevent the onset of heart failure.…”
Section: Discussionmentioning
confidence: 96%
“…Higher expression levels of STRA6 are observed in the brain, kidneys, spleen, testes, and female genital tract 76 . Indeed, increased expression of CLOCK protein is also detected in the kidneys but not in the liver of 5/6Nx mice 24 , 26 . Therefore, retinol-induced expression of CLOCK protein may be dependent on the levels of STRA6.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations